Observations of Extreme Waves and Wave Spectra during Hurricane Dorian (2019) - Bethel, Brandon J. (International Journal of Bahamian Studies, 2023)
Due to the sparse distribution of buoys in the ocean, direct observations of extreme wave activity as excited by tropical cyclones (TCs) are few; but nonetheless, these buoys provide rare opportunities to learn more about how weather systems interact with the ocean wave field. In this study, National Oceanic and Atmospheric Administration National Data Buoy Center buoy observations of one-dimensional (1D) and two-dimensional (2D) wave spectra during the translation speed of Hurricane Dorian (2019) through the Atlantic Ocean were used to examine extreme wave events in the days before and after its September 1, 2019 landfall in The Bahamas. Observations of wave properties during storm intensification and decay showed that although significant wave height naturally rose and fell, the dominant wave period remained virtually constant. At the height of the storm, a lethal combination formed, with the highest significant wave heights being recorded at over 8 m (more than four times the mean) and dominant wave periods exceeded 12 s. Wave direction also varied widely as wave regimes shifted from wind-sea to swell, with spectral wave energy peaking at over 120 m2/Hz, six times higher than pre-Hurricane Dorian wave states. This study provides the first in situ characterization of extreme wave heights as induced by Hurricane Dorian. The study recommends that a number of observational platforms be funded, developed, and deployed throughout the Lucayan Archipelago.